Stable p/n‐Dopable Conducting Redox Polymers for High‐Voltage Pseudocapacitor Electrode Materials: Structure–Performance Relationship and Detailed Investigation into Charge‐Trapping Effect. Issue 21 (18th July 2017) - Zhang, Huanhuan; Yao, Mingming; Wei, Jinbei; Zhang, Yuewei; Zhang, Shitong; Gao, Yu; Li, Jinyu; Lu, Ping; Yang, Bing; Ma, Yuguang
Abstract: P/n‐dopable conducting polymers (CPs) are considered as the most promising choice for CP‐based supercapacitor electrode materials, as they can work at a voltage wider than 2 V and store energy several times greater than that of only positively dopable CPs. However, such electrode materials suffer severe cycling instability during a charge–discharge process. In this paper, two conducting redox polymers with different linkage modes are designed and prepared, with redox moieties embedded in the backbone or grafted as pendant groups, as p/n‐dopable electrode materials for supercapacitor. In addition to the voltage and energy advantages of p/n‐dopable electrode materials, these two conducting redox polymers show excellent cycling stability. Supercapacitors based on the polymer with backbone‐graft structure show better cycling stability, remaining 83% of initial capacitance after 2000‐cycle charge–discharge test. The relationship between the charge‐trapping (CT) effect that often occurs during the doping processes of p/n‐dopable CPs and performance degradation is investigated in detail. Results show that the CT effect occurring during the n‐doping process is probably the main cause of performance degradation. The degradation caused by the CT effect may be recovered partially or almost totally by several cyclic voltammetry scans, thereby extending the lifetime of supercapacitor devices to some degree. Abstract : P/n‐dopable conducting redox polymers with two different link modes are designed and prepared as pseudocapacitor electrode materials. The effects of polymer structure on the electrochemical behaviors, doping processes, and supercapacitor performance are systematically investigated. Supercapacitor prototypes with improved cycling stability are achieved, and degradation caused by charge‐trapping effect is explained in detail.